A development of Islamic e-commerce ethics model - Nor Hapiza Mohd Ariffin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this paper is to study the Islamic ethical elements in online e-Commerce (EC) transactions and develop an ethical business model. Based on a preliminary investigation, it was found that sellers who use EC were not aware and did not have proper guideline to guide them on the Islamic business ethics during online transactions. This paper aims to propose an Islamic EC Ethics model to increase the awareness among businesses in EC transactions. Both qualitative and quantitative methods were deployed as the primary method where experts were interviewed, and questionnaire were distributed. Using selective sampling method, data collection from 100 respondents who have performed online selling transactions were collected. Statistical Package for Social Science (SPSS) was used to analyze the data collected and followed by model development. Finally, it was validated by an expert. The proposed Islamic EC ethics model provides proper guideline for online sellers while performing online transactions by guide them about the right and wrong things to do in accordance to Islamic beliefs.